SISTEM REKOMENDASI PEMBERIAN KAPUR DOLOMIT BERDASARKAN KADAR KEASAMAN TANAH BERBASIS INTERNET OF THINGS (IoT) - Ely Nuryani; Huswatun Hasanah; Widyawati Widyawati; Irma Yunita Ruhiawati; Nurul Hidayah (Jurnal Sistem Informasi dan Informatika (Simika), 2025)
The green revolution helped increase food production by intensifying existing land so that it could provide synthetic nutrients. However, synthetic fertilizers make plants vulnerable to pests and other hazards. This causes living things that help decompose the soil to be vulnerable to death due to the use of synthetic pesticides. The longer the use of these pesticides causes the soil to become damaged without any improvement. One indicator is a decrease in acidity levels, which should be a neutral pH of 7. Therefore, this study created a system that can be used to detect the acidity level of agricultural land. The location of the research object is agricultural rice fields in Serang Regency, Banten Province. The equipment used to support the IoT-based system includes a soil pH sensor, NodeMCU ESP8266, 3. Switch, and 9v Battery. The system development method uses the waterfall method and is IoT-based so that soil acidity levels can be monitored remotely. Based on the trial results, the system can measure and monitor soil acidity conditions remotely easily, quickly, and accurately. This system can help and facilitate farmers in making decisions about the appropriate use of dolomite lime for land that tends to be acidic.